Feasibility study of the CECO wave energy converter - João Marinheiro (2015)
A feasibility study and proof of concept of a new and patented wave energy converter called CECO was performed. This device was designed to absorb both the kinetic and the potential wave energy. The behavior of CECO was analyzed for different wave conditions and operation modes, and two different techniques were used to evaluate the absorbed power. The relative capture widths determined for this not-yet-optimized model are relatively high (up to 30%) and proved that this concept is promising, thus justifying further optimization studies.